2016
DOI: 10.1590/1980-5373-mr-2015-0673
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure in Al-Si-Cu System Modified with a Transition Element Addition and its Effect on Hardness

Abstract: The effect of Ni 1-2 wt.% addition on the microstructure and hardness of the aged A319 alloy were studied. Characterization analyses by x-ray diffraction, optical microscopy and scanning electron microscopy suggest clearly that Ni addition forms Al-Ni-Cu-Fe, Al-Cu-Ni and Al-Ni intermetallic compounds that correlates well with equilibria conditions. Analyses by transmission electron microscopy show that aging heat treatment promotes microstructural changes in morphology, size, and spatial distribution of precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…This decrease in hardness, or softening of the alloy, is reflected through the observed decrease in the hardening parameters σ f , σ y and χ and an increase in ε f given in Figure 1. The thermally induced internal structure of the alloy in the tested temperature range which leads to the observed hardening behavior up to 525 K after which a softening behavior dominates, consists with previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Figure 2 (A-c): the Electron Micrographs Performance For Sisupporting
confidence: 82%
See 1 more Smart Citation
“…This decrease in hardness, or softening of the alloy, is reflected through the observed decrease in the hardening parameters σ f , σ y and χ and an increase in ε f given in Figure 1. The thermally induced internal structure of the alloy in the tested temperature range which leads to the observed hardening behavior up to 525 K after which a softening behavior dominates, consists with previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Figure 2 (A-c): the Electron Micrographs Performance For Sisupporting
confidence: 82%
“…In aluminum alloys, some transition metals like Ni and Fe, and some rare earths like Ce, which the main characteristic is their low solubility in Al e.g. maximum of 0.01% to 0.04%, are employed in Al-Cu and Al-Si alloys to improve strength and hardness at elevated temperature [4][5][6][7]. This is correlated mainly to impact its coefficient of thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The solidification thermal parameters have influence on the microstructure and microsegregation andthese, in turn, are key featuresin inducing non-uniformity on the as-cast material mechanical properties. For this reason, the microstructure and microsegregation has been extensively studied both theoretically [1][2][3][4][5][6][7][8][9][10][11] and experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25] for the last decades. The Al-1.2wt%Pb and Al-3.2wt%Bi alloys have been chosen by Freitas et al 13 , to study the effect of microstructural parameters on the wear process.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental researches have been proposed for binary alloys of metallurgical interest. However, experimental works focused on the multicomponent alloys are still rare in the literature 1,17 . The present experimental paper is based on the research line of previous references, highlighting the correlation between the thermal parameters and tertiary dendrite arm spacing (λ 3 ) and microsegregation during solidification of a ternary Al-9.0wt%Si-4.0wt%Cu alloy under unsteady-state heat flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, additions of 1 to 2% Ni to 2xxx and 3xxx series alloys improve hardness and tensile properties at elevated temperatures [2]. Hayajneh et al [3] and others investigations [4] have been reported the effect of Ni additions in the hardness properties in Al-Cu and Al-Si-Cu alloys respectively; they reported that the formation of the Al-Ni, Al-Ni-Cu intermetallic compounds have a direct relationship with mechanical properties and a significant delay in the loss of hardness values during the over-aging stage.…”
mentioning
confidence: 99%